Evaluating methods and factors that affect dicamba volatility - Carbonari, Caio A. [UNESP]; Costa, Renato N. [UNESP]; Giovanelli, Bruno F. [UNESP]; Velini, Edivaldo D. [UNESP] (My University, 2022)
Background: Dicamba is a herbicide with a moderate volatility profile and low dose effects on broadleaf weeds. Dicamba volatility can be strongly reduced with formulation technology and volatilization reducers. Objective: This literature review on the dicamba herbicide aims to present new perspectives for its use, characteristics, volatilization risks, technologies to mitigate these risks and the main methods used to assess volatility in Brazil and worldwide. Conclusions: Dicamba volatility can be mitigated with appropriate formulations and/or the use of adjuvants to reduce volatility. There has been an evolution in adapting new salts and technologies to reduce dicamba volatility. There are different methods of evaluating herbicide volatility, in particular, for the quantification of volatilized dicamba either in laboratory or field studies. Available methods can be fast and consistent and can assess volatilization from different surfaces, weather conditions and technologies to reduce volatilization. Under some conditions it is desirable to combine this method with bioassays.
Keywords: auxinic herbicide; dicamba formulation; environmental risk; volatilization